JADIDISM PHILOSOPHY AND THE ISSUES OF STRENGTHENING SOCIAL STABILITY IN MODERN SOCIETY (Modern American Journal of Social Sciences and Humanities, 2026)
This article examines the philosophical foundations of the Jadid movement and its significance in strengthening social stability in contemporary society. Particular attention is paid to the educational, cultural, and socio-political ideas of Jadid thinkers, who regarded enlightenment, national consciousness, and moral development as essential factors of social progress. The study analyzes the relevance of Jadid philosophy in addressing modern challenges such as globalization, cultural transformation, youth education, and social cohesion. The findings suggest that the Jadids’ emphasis on knowledge, reform, tolerance, and national identity remains an important intellectual resource for promoting sustainable development and strengthening social stability in the modern world.